Origin of internal flow structures in columnar-jointed basalt from Hrepphlar, Iceland I.: Textural and geochemical characterization ... - Bosshard, Sonja A.; Mattsson, Hannes B.; Hetényi, György (ETH Zurich, 2012)
Bulletin of Volcanology, 74 (7) ... : ISSN:0258-8900 ...